Penerapan Posisi Head Up 30 dengan Relaksasi Benson terhadap Penurunan Kapasitas Adaptif Intrakranial pada Pasien Intra Cerebral Hemorrhage (ICH) - Erwina Christias; Arlies Zenitha Victoria (STIKES Telogorejo Semarang, 2025)
Emergency hypertension is an increase in blood pressure ≥180/120 mmHg accompanied by new or worsening damage to the target organ, and is the main factor in the occurrence of Intracerebral Hemorrhage (ICH). ICH is an intracranial hemorrhage due to a rupture of blood vessels in brain tissue. Based on Riskesdas data, there are around 100 thousand cases of emergency hypertension that have an impact on ICH in Indonesia. Proper management, both pharmacological and non-pharmacological, is very necessary. Nonpharmacological interventions such as 30° head up position and Benson's relaxation can help lower intracranial pressure (ICT). The 30° head up increases blood flow to the brain and prevents an increase in ICT, while Benson's relaxation lowers the activity of the sympathetic nervous system, dilates arteries, and facilitates tissue oxygenation. The purpose of this paper was to analyze the application of 30° head up nursing interventions and Benson relaxation in ICH patients with decreased intracranial adaptive capacity. The results of the study showed blood pressure of 185/95 mmHg, MAP of 118 mmHg, and the results of the CT-Scan showed ICH in the thalamus to the right radial corona. The intervention was carried out for three days and proved effective in reducing ICT. This scientific paper is expected to improve the quality of neurological nursing care as well as understanding and critical thinking skills in handling ICH cases.